Extrapolation of design strategies for lignocellulosic biomass conversion to the challenge of plastic waste. (18th January 2022) - Jarboe, Laura R; Khalid, Ammara; Rodriguez Ocasio, Efrain; Noroozi, Kimia Fashkami
Abstract: The goal of cost-effective production of fuels and chemicals from biomass has been a substantial driver of the development of the field of metabolic engineering. The resulting design principles and procedures provide a guide for the development of cost-effective methods for degradation, and possibly even valorization, of plastic wastes. Here, we highlight these parallels, using the creative work of Lonnie O'Neal (Neal) Ingram in enabling production of fuels and chemicals from lignocellulosic biomass, with a focus on ethanol production as an exemplar process.